The public library as a community service in a developing society : case study of Botswana. - Nkabinde, Thokozile M. N. (2012)
This study evaluates the purpose and role of the public library in national development in Botswana. Particular attention is focused on the public library as a community resource as well as its sensitivity in meeting the needs of community members and of organizations operating in the community. Chapter 1 introduces the nature of the problem, and brief historical and current developments of the public library in Botswana. Research objectives of the study are also outlined. Chapter 2 attempts to locate the public library in developing countries within development strategies such as the modernization and basic needs approach. Discussions further illustrate how policies emanating from these development strategies have influenced public library policies in these countries, and in Botswana. Attempts are made to show how the public library in Botswana is trying to adjust to shifts in emphasis of government development plans, especially the rural development emphasis. Chapter 3 outlines methods of research used to collect and process data obtained from the village Molepolole in Botswana. There is a brief discussion of the nature of this village as well as that of the community public library. Chapter 4 and 5 present findings of the household survey, and of community organizations and public librarians interviewed. An analysis and interpretation of findings of the household survey based on a sample of 203 readers drawn from the village is also presented. Community organizations interviewed include both government and non-government. Patterns of reading and views on the library of both readers in the survey and public library users, are explored. Chapter 6 presents a brief review of developments of the national campaign to eradicate illiteracy in Botswana, which was launched by the Department of Non-formal Education (DNFE) in 1970. The study shows what role the public library has been, and what it should be, in the provision of effective support for the promotion of literacy and reading. The last chapter gives a summary of findings, and suggests a model that could be adopted to develop an effective rural public library service in Botswana. The model is based on principles of the basic needs approach to development, which emphasizes appropriateness, focus on target groups, accessibility, affordability, integrativeness, participation and assertiveness. === Thesis (M.Soc.Sci.)-University of Natal, Durban, 1988.